An overview of clinical associate roles in the neurointerventional specialty. (5th January 2015) - Chittle, Melissa D; Vanderboom, Teresa; Borsody-Lotti, Judith; Ganguli, Suvranu; Hanley, Patricia; Martino, JoAnne; Mueller, Peter; Penzias, Alexandra; Saltalamacchia, Catherine; Sheridan, Robert M; Hirsch, Joshua A
Abstract : Neurointerventionalists have long partnered with certain types of clinical associates to provide longitudinal care. This overview summarizes differences in education, background, roles, and scopes of practice of the various clinical associates (physician assistants, nurse practitioners, clinical nurse specialists, radiology practitioner assistants, radiologist assistants, and nursing care coordinators). Key differences and similarities are highlighted to alleviate confusion about the roles clinical associates can assume on a neurointerventional service. This overview is intended to guide practices as they consider broadening their clinical support teams.